Role of pressure in flow‐induced shish‐kabab in binary blend of long‐ and short‐chain Polyethylenes. Issue 3 (12th February 2019) - Zhang, Xi‐Xi; Yang, Shu‐Gui; Hua, Wen‐Qiang; Lin, Jian‐Mei; Lei, Jun; Bian, Feng‐Gang; Xu, Ling; Li, Zhong‐Ming
Abstract: Long polymer chains are admittedly beneficial for formation of flow‐induced shish‐kebabs, but up to now, the role of pressure, one major polymer processing parameter, in flow‐induced shish‐kebab is not touched. In the current work, bulk polyethylene (PE) and blend of 98 wt% PE and 2 wt% linear ultra‐high molecular weight polyethylene (LUHMPE/PE) were used as model polymers. Utilizing the pressuring and shearing device (PSD), the combined effect of pressure and long chains on flow‐induced shish‐kebab was revealed for the first time. Under a pressure of 50 MPa, there was no trace of shish‐kebab over the entire range of applied shear rates (0.5‐28.3 s −1 ). As the pressure increased to 75 MPa, shish‐kebab was induced by flow at 28.3 s −1 for PE, while shish‐kebab appeared in LUHMPE/PE blends at 15.7 s −1 . Undoubtedly, the pressure significantly facilitated the formation of shish‐kebab and revealed a synergistic effect on flow‐induced shish‐kebab when cooperating with long chains. Our research not only demonstrates the importance of pressure conditions in flow‐induced crystallization, but also provides more valuable data for actual processing. Abstract : There is a synergistic effect between applied pressure and long polyethylene chains on flow‐induced shish‐kebab. At 50 MPa, no shish‐kebab can be found in polyethylene short‐chains (PE) and long−/short‐chain blends (LUHMPE/PE). Whereas, at 75 MPa, shish‐kebab structures are abundant in the LUHMPE/PE blends at the shear rate of 28.3 s −1, which is ascribed to the stabilizing effect of pressure on shear‐induced long chains.